THE EFFECT OF CHATGPT-ASSISTED GRAMMAR INSTRUCTION ON EFL LEARNERS' GRAMMATICAL ACCURACY - Abdurauf Bozorov Sheramatovich (International Journal of Literature and Language Studies, 2026)
The emergence of generative artificial intelligence has created new opportunities for language learning and instruction. Among AI-powered tools, ChatGPT has attracted considerable attention due to its ability to provide immediate feedback, personalized explanations, and interactive learning experiences. This study investigates the effect of ChatGPT-assisted grammar instruction on the grammatical accuracy of English as a Foreign Language (EFL) learners. Drawing upon the Noticing Hypothesis and corrective feedback theory, the study examines whether AI-generated feedback can facilitate grammar acquisition more effectively than traditional instructional methods. A quasi-experimental design involving an experimental group and a control group was employed. Results indicate that learners who received ChatGPT-assisted instruction demonstrated greater improvement in grammatical accuracy than those who received conventional instruction. The findings suggest that ChatGPT can serve as an effective supplementary tool for grammar learning by promoting error awareness, learner autonomy, and individualized practice. However, AI-generated feedback should complement rather than replace teacher guidance. The study contributes to the growing literature on artificial intelligence in language education and offers practical implications for integrating AI technologies into EFL classrooms.